Cascadic Multigrid Method for the Mortar Element Method for $P_1$ Nonconforming Element (Journal of Computational Mathematics, 2005)
In this paper, we consider the cascadic multigrid method for the mortar $P_1$ nonconforming element which is used to solve the Poisson equation and prove that the cascadic conjugate gradient method is accurate with optimal complexity.
Keywords: Mortar $P_1$ nonconforming element; Cascadic multigrid method.